Modeling supermarket re-layout from the owner's perspective - Boros, Peter; Feher, Orsolya; Lakner, Zoltan; Niroomand, Sadegh; Vizvari, Bela (Springer, 2016)
It is well-known that if a customer follows a longer path while shopping then the expected value of his/her purchased amount is increased; therefore the sale amount of the supermarket can be increased. This study deals with a new problem: how to re-layout a supermarket the impulsive purchases of the average customer are maximized. Supermarket is a shop of limited size and is definitely smaller than the hypermarket. It is assumed that it is located in a living area and customers know its layout well. In many countries, there are plenty of shops like that. In a case study 27 clusters of customers are defined based on 13,300 real buying. To assume that actors behave in a rational way, is traditional in analysis of economic problems. Rationality means in that case that customers choose the shortest possible path according to their a priori purchase plan. Thus, traveling salesman problem (TSP) can be used to simulate the customer's shopping path. Dantzig-Fulkerson-Johnson formulation of TSP is used to maximize the shortest traveled path of each customer type by rearranging the items of the supermarket as a max-min problem. The computational experiences on the case study show that the total distance is increased in the new layout proposed by the model.
Keywords: Supermarket layout; Customer behavior; Mixed integer linear programming; Traveling salesman problem; Dantzig-Fulkerson-Johnson model